Study of the Applicabilty of Content Uniformity and Dissolution Variation Test on Ropinirole Hydrochloride Tablets - Edina Vranić; Alija Uzunović (Biomolecules & Biomedicine, 2008)
When considering single-dose preparations, it is fundamental that the patient receives in his individual dose an amount of drug close to that claimed on the label. Since drug content and content uniformity of single-dose preparations depend on a number of processes associated with their manufacture, it is obviously unrealistic to expect every unit of product to possess exactly the same amount of the active ingredient. For that reason, pharmacopeial standards and specifications have been established to provide limits for permissible variations in the amount of active ingredient of individual single-dose units. The aim of our study was to determine the applicability of content uniformity and dissolution variation test on ropinirole hydrochloride tablets. According to the results obtained, we may conclude that analyzed ropinirole hydrochloride tablets satisfied pharmacopeial requirements concerning content uniformity and dissolution testing. In this case RSD tended to increase with the decrease of the labeled strength. It is obvious from the R1 value, as well. On the other side, if consider larger number of lots, analyzed by different assay methods and various sample preparation procedures this correlation is less pronounced. This may be a consequence of different assay techniques applied, HPLC, UV-D1 or UV